Henry Hotze, Confederate propagandist : selected writings on revolution, recognition, and race - Hotze, Henry, 1833-1887 (University of Alabama Press, 2008)
Consists of a biographical essay on Henry Hotze; his contributions to Mobile newspapers during his military service in 1861; his correspondence with Confederate officials during his service in London; articles he published in London to influence British and European opinion; and his correspondence with, and published work in support of, Gobineau.